PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY DAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA SMA NEGERI 7 KUPANG - Pau, Depi (Universitas PGRI Sumatera Barat, 2019)
AbstractThis research is an experimental research with Pretest-Posstest Comparison Group Design. Research conducted at SMA Negeri 7 Kupang for class XI MIA. The purpose of this research was (1) to determine the differences of student’s physics problem solving abilities between those who taught using Guided Inquiry learning model with those who taught using problem based learning model. This research also (2) aim to find out whether the physics problem solving abilities of students taught using the Guided Inquiry learning model are higher than those students who taught using problem based learning model. Population of this research is all class XI MIA of SMA Negeri 7 Kupang, with simple random technique as sampling method. Student’s problem solving abilities datas obtained from the instrument use essay questions pre-test and post-test.The results showed that: 1) There are significant differences in students' physics problem solving abilities between students taught using the Guided Inquiry learning model 2) Physics problem solving abilities of students taught using the Guided Inquiry learning model were higher than students who were taught using Problem Based Learning learning models Keywords: Guided Inquiry Model, Problem Based Learning Model, Problem Solving Ability ABSTRAK Penelitian ini merupakan jenis penelitian eksperimen dengan desain penelitian Pretest-Posttest Comparison Group Design yang dilakukan di kelas XI MIA SMA Negeri 7 Kupang pada tahun ajaran 2019/2020. Tujuan dari penelitian ini adalah (1) untuk mengetahui adanya perbedaan kemampuan pemecahan masalah fisika siswa yang diajar menggunakan model pembelajaran Guided Inquiry dengan siswa yang diajar menggunakan model pembelajaran Problem Based Learning, serta (2) untuk mengetahui apakah kemampuan pemecahan masalah fisika siswa yang diajar menggunakan model pembelajaran Guided Inquiry lebih tinggi daripada siswa yang diajar menggunakan model pembelajaran Problem Based Learning. Populasi dalam penelitian ini adalah seluruh kelas XI MIA SMA Negeri 7 Kupang, dengan pengambilan sampel yang dilakukan menggunakan teknik simple random sampling. Data kemampuan pemecahan masalah diperoleh dari instrumen soal essay pre-test dan post-test. Hasil penelitian menunjukan bahwa; 1) Terdapat perbedaan kemampuan pemecahan masalah fisika siswa yang signifikan antara siswa yang diajar menggunakan model pembelajaran Guided Inquiry dengan siswa yang diajar menggunakan model pembelajaran Problem Based Learning 2) kemampuan pemecahan masalah fisika siswa yang diajar menggunakan model pembelajaran Guided Inquiry lebih tinggi daripada siswa yang diajar menggunakan model pembelajaran Problem Based Learning yang. Kata Kunci: Model Pembelajaran Guided Inquiry, Model Pembelajaran Problem Based Learning, Kemampuan Pemecahan Masalah